Students’ observed engagement in lessons, instructional activities, and learning experiences - Heemskerk, Christina Hubertina Helena Maria; Malmberg, Lars-Erik (Frontline Learning Research, 2020)
In order to expand previous intraindividual studies of student engagement we investigated students’ observed engagement (i.e., on- and off-task behaviour), instructional activities (i.e., teacher-led whole class, individual work, pair-work, student-teacher interaction, assessment, and ”other”), and self-reported learning experiences (cognitive engagement, difficulty, competence, emotional engagement, positive and negative emotions), within lessons during one calendar week. Eighteen fourth and fifth grade target students (Mage=10.1, SD=0.44) were observed every 30 sec during two to four lessons each day for five school days (engagement and instructional activities), on average 66.05 times per lesson (SD=19.16, Range=15-80, nobs=14,994) between 9-18 lessons during a week. Simultaneously, students provided 1-3 electronic questionnaire self-reports per lesson (Mself_report=35.1, SD=12.6, Range=19-52, nself_report=631). We regressed observed engagement (0 = off-task, 1 = on-task) on self-reported learning experiences using 3-level (time-points nested in lessons, nested in students) Bayesian logistic regression models in brms. Observed engagement diminished during lessons, and was predicted by higher cognitive engagement, and instructional activities. As compared to teacher-led instruction, engagement was higher during individual tasks, teacher-supported tasks, and assessments. Overall self-reported and observed engagement within lessons converged, supporting their use in intraindividual research.